2010
DOI: 10.1128/mcb.00150-10
|View full text |Cite
|
Sign up to set email alerts
|

Differential NDR/LATS Interactions with the Human MOB Family Reveal a Negative Role for Human MOB2 in the Regulation of Human NDR Kinases

Abstract: MOB proteins are integral components of signaling pathways controlling important cellular processes, such as mitotic exit, centrosome duplication, apoptosis, and cell proliferation in eukaryotes. The human MOB protein family consists of six distinct members (human MOB1A [hMOB1A], -1B, -2, -3A, -3B, and -3C), with hMOB1A/B the best studied due to their putative tumor-suppressive functions through the regulation of NDR/LATS kinases. The roles of the other MOB proteins are less well defined. Accordingly, we chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
124
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(126 citation statements)
references
References 40 publications
2
124
0
Order By: Relevance
“…Interestingly, the interaction between MOB proteins (the human genome encodes six MOBs: MOB1A/B, MOB2, and MOB3A/B/C) and the N-terminal regulatory domain of the kinases is a common feature of NDR family kinases, although LATS1/2 and NDR1/2 appear to use distinct subsets of MOB proteins. MOB1A/B associate with both LATS1/2 and NDR1/2, while MOB2 mediates an inhibitory interaction with NDR1/2 but not with LATS1/2 Bothos et al 2005;Hergovich et al 2005;Kohler et al 2010).…”
Section: Mechanisms Of Hippo Kinase Cascade Activationmentioning
confidence: 97%
“…Interestingly, the interaction between MOB proteins (the human genome encodes six MOBs: MOB1A/B, MOB2, and MOB3A/B/C) and the N-terminal regulatory domain of the kinases is a common feature of NDR family kinases, although LATS1/2 and NDR1/2 appear to use distinct subsets of MOB proteins. MOB1A/B associate with both LATS1/2 and NDR1/2, while MOB2 mediates an inhibitory interaction with NDR1/2 but not with LATS1/2 Bothos et al 2005;Hergovich et al 2005;Kohler et al 2010).…”
Section: Mechanisms Of Hippo Kinase Cascade Activationmentioning
confidence: 97%
“…In both flies and mammals, MOB1 proteins regulate both the NDR and the LATS branch, 5,[15][16][17][18][19][20] whereas the MOB2 protein specifically regulates the NDR branch. 6,15 Interestingly, it has been shown that in mammals and potentially also in flies, the MOB2 protein functions as an inhibitor of NDR signaling. 6 Furthermore, in D. melanogaster, one Ste-20-like kinase, Hippo (Hpo), can regulate both NDR/ LATS kinase family members.…”
Section: Functions Of Mammalian Ndr Kinases In Tumor Suppression: An mentioning
confidence: 99%
“…6,15 Interestingly, it has been shown that in mammals and potentially also in flies, the MOB2 protein functions as an inhibitor of NDR signaling. 6 Furthermore, in D. melanogaster, one Ste-20-like kinase, Hippo (Hpo), can regulate both NDR/ LATS kinase family members. 8 Similar findings have been reported for the Ste-20-like kinases (MST kinases) in mammals.…”
Section: Functions Of Mammalian Ndr Kinases In Tumor Suppression: An mentioning
confidence: 99%
See 2 more Smart Citations